Condition of lipid metabolism at women of genesial period and its correlation with functional activity of thyroid gland and ovary - V. I. Korchin; E. V. Korneeva (Бюллетень сибирской медицины)
In the present work all possible correlations between functional status of thyroid gland, ovaries and lipids of Serum of blood at women of genesial period living in Far North for a long time are investigated. In the process of investigation there was indentified that women with cyst of ovary have a rise of general cholesterol and cholesterol of lypoproteid of low solidity.